Routine noninvasive prenatal screening for fetal RHD in plasma of RhD‐negative pregnant women—2 years of screening experience from Denmark. (13th June 2014) - Banch Clausen, F.; Steffensen, R.; Christiansen, M.; Rudby, M.; Jakobsen, M. A.; Jakobsen, T. R.; Krog, G. R.; Madsen, R. D.; Nielsen, K. R.; Rieneck, K.; Sprogøe, U.; Homburg, K. M.; et al.
ABSTRACT Objective Prenatal and postnatal RhD prophylaxis reduces the risk of RhD immunization in pregnancies of RhD‐negative women. Based on the result from prenatal screening for the fetal RHD gene, prenatal RhD prophylaxis in Denmark is targeted to RhD‐negative women who carry an RhD‐positive fetus. Here, we present a 2‐year evaluation of a nationwide prenatal RHD screening. Methods Blood samples were drawn from RhD‐negative women in gestational week 25. DNA was extracted from maternal plasma and analyzed for the RHD gene. The prenatal RHD results were compared with the serological typing of newborns in 12, 668 pregnancies. Early compliance was assessed for 690 pregnancies. Results The sensitivity for the detection of fetal RHD was 99.9% (95% CI: 99.7–99.9%). Unnecessary recommendation of prenatal RhD prophylaxis was avoided in 97.3% of the women carrying an RhD‐negative fetus. Fetuses that were seropositive for RhD were not detected in 11 pregnancies (0.087%). The sample uptake percentage was 84.2%, and the compliance for prenatal anti‐D administration was 93.2%. Conclusion The high sensitivity, maintained over 2 years, underlines the reliability of routine prenatal fetal RHD screening in RhD‐negative pregnant women, specifically at 25 weeks of gestation. The remaining challenges are logistical and are related to program compliance. © 2014 John Wiley & Sons, Ltd.